Inhibitory effect of 1-methyldodecyldimethylamine oxide and N,N-bis(dodecyldimethyl)-1,2-ethanediammonium dibromide on the spores of Bacillus cereus - Cupková, V; Vinter, V; Devínsky, F; Lacko, I; Mlynarcík, D (Folia microbiologica, 1988)
1-Methyldodecyldimethylamine oxide (MDDO) and N,N'-bis(dodecyldimethyl)-1,2-ethanediammonium dibromide (BDED) exhibit a significant affinity for the surface of Bacillus cereus spores and adsorb very rapidly to the cells; they have a pronounced inhibitory effect on spore outgrowth. In order to alter the affinity of the spore surface for these inhibitors, the spores were pretreated with sodium dodecyl sulfate (SDS), and with an electronegative (Tween 80) and electropositive (histone) compound. In SDS-pretreated spores the inhibitory effect of MDDO and BDED was abolished to a considerable extent. Whereas the development of intact spores was inhibited already after germination, in SDS-pretreated spores the postgermination development continued but was not completed. In Tween 80-pretreated spores the addition of BDED led only to a retardation of outgrowth and division; BDED added only during the division stage interrupted further development completely. Histone-pretreated spores stopped their development instantaneously after the addition of BDED at any phase of the postgermination development. The possible mechanisms of the interaction of the compounds used with spore surface or rather with the state of its structures are discussed.
Keywords: Quaternary Ammonium Compounds; Bacillus cereus; spory bakteriální; Spores, Bacterial; Dimethylamines; kvartérní amoniové sloučeniny; dimethylaminy